A photometric study of the old open clusters Berkeley 73, Berkeley 75 and Berkeley 25 - Carraro, G. (2005)
CCD BVI photometry of the faint open clusters Berkeley 73, Berkeley 75 and Berkeley 25 are presented. The two latter are previously unstudied clusters to our knowledge. While Berkeley 73 is found to be of intermediate-age (about 1.5 Gyr old), Berkeley 75 and Berkeley 25 are old clusters, with ages greater than 3.0 Gyr. We provide also estimates of the clusters size. All these clusters lie far away from the Galactic Center, at R GC ≥ 16 kpc, and quite high on the Galactic plane, at |Z ⊙ | ≥ 1.5 kpc. They are therefore important targets to probe the properties of the structure of the Galaxy in this direction, where the Canis Major over-density has been discovered to be located.